Parlament polski w opinii Józefa Piłsudskiego 1918-1930 - Mucha, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2001)
Józef Piłsudski at his 51, succeeded to the office of the Temporary Chief of the State on November 22nd 1918. He was expected to be on the post till the first session of the parliament that only was to be elected. Nevertheless it was his decision to announced the elections and convoke the parliament as soon as possible. Doing that J. Piłsudski was looking mainly for the legitimisation of his power by the democratic representation of the people, and not by the organ in which the sovereignty of the restitution state was fixed. We can presume that he did not believe in fact that this body was able to represent an authentic wish of the nation. He was convinced that he had understood himself the true interests of the people correctly enough to be able to act in the name of the nation. On the other hand the Seym (Polish Parliament) that had been elected, treated its post seriously considering itself the only sovereign of the Republic of Poland. This difference of views on the political roles contributed very much to the future conflicts. It was an important factor that created Piłsudski’s opinion on the function of parliament in the political system of the state. There were four questions in Pilsudski’s views concerning the parliament. The first one was connected with the opinions about the particular Seyms. He depreciated all of them, gave them sarcastic epithets, unjust accusations and invectives. In his other public speeches Piłsudski made the differences between the Parliament as an institution and its members as the individuals. According to his views however the parliament as an element of the political system of the state was useless, but still more useless was the individual member of parliament about whom his opinion was even worst. The third question very much underlined in Piłsudski’s speeches was the place of parliament determined by the March constitution. In his eyes there was no excuse for the position of the parliament as the first and most important element of the state political system. To the contrary - he was convincod that the position of both Houses of Parliament as it was fixed by the constitution, could produce nothing but bad results for the state and just a catastrophe as far as the power of the president was concerned. Last but not least he formulated comprehensive opinions about the parliamentary system in general and about the Polish one in particular. He maintained that the parliamentary system was in a deep crisis in the world. He said that the Polish parliament was extremely and incurably ill, and that as an institution it was hated by the society. In those circumstances there is nothing surprising in the fact that it was in Pilsudski’s political environment where the idea of depriving the parliament of its most important attributes and minimising its influence on the political life of the country was born. I t was the main direction of changes introduced by the constitution of April 1935. The postulate of Piłsudski was then realised by that constitution. The Seym still existed but without the real power and influence on the government of the state. In a great part it preserved only the externals of the real parliament.